Heart Failure With Preserved Ejection Fraction and Adipose Tissue: A Story of Two Tales - Oh, Albin; Okazaki, Ross; Sam, Flora; Valero-Muñoz, Maria (Frontiers in Cardiovascular Medicine, 2019)
Heart failure with preserved ejection fraction (HFpEF) is characterized by signs and symptoms of heart failure in the presence of a normal left ventricular ejection fraction. Although it accounts for up to 50% of all clinical presentations of heart failure, there are no evidence-based therapies for HFpEF to reduce morbidity and mortality. Additionally there is a lack of mechanistic understanding about the pathogenesis of HFpEF. HFpEF is associated with many comorbidities (such as obesity, hypertension, type 2 diabetes, atrial fibrillation, etc.) and is coupled with both cardiac and extra-cardiac abnormalities. Large outcome trials and registries reveal that being obese is a major risk factor for HFpEF. There is increasing focus on investigating the link between obesity and HFpEF, and the role that the adipose tissue and the heart, and the circulating milieu play in development and pathogenesis of HFpEF. This review discusses features of the obese-HFpEF phenotype and highlights proposed mechanisms implicated in the inter-tissue communication between adipose tissue and the heart in obesity-associated HFpEF.